Steroids and Mortality in Non‐Critically Ill Covid‐19 Patients: A Propensity Score‐Weighted Study in a Chilean Cohort - Beltran-Buendia, C; Vargas-Rona, C; Zamora-Vargas, F; Raijmakers-Hidalgo, M; Silva-Ayarza, I (Elsevier B.V., 2021)
Objectives: The aim of this study was to evaluate the impact on 30-day mortality of early use of corticosteroids in COVID-19 patients with supplementary oxygen requirements and without invasive mechanical ventilation at the initiation of therapy. Methods: All patients hospitalized with COVID-19 between April 15 and July 15, 2020, and requiring supplementary oxygen, were prospectively included in a database. Patients who died or required intubation within the first 48 hours were excluded. Patients who received corticosteroids within the first 5 days of hospitalization and at least 24 hours prior to intubation were allocated to the ‘early corticosteroids’ group. To compare both populations and adjust for non-random treatment assignment bias, a weight-adjusted propensity score model was used. Results: In total, 571 patients met the inclusion criteria, 520 had sufficient information for the analysis. Of these, 233 received early corticosteroids and 287 did not. Analysis showed a reduction of 8.5% (p = 0.038) in 30-day mortality in the early corticosteroid group. The reduction in mortality was not significant when patients with corticosteroid initiation between day 5 and day 8 of hospitalization were included. Conclusion: Early corticosteroid use reduced mortality in patients with pneumonia due to COVID-19, who required supplementary oxygen but not initial invasive mechanical ventilation. © 2021 The Author(s)